2021
DOI: 10.3892/or.2021.8232
|View full text |Cite
|
Sign up to set email alerts
|

FGD5‑AS1 is an oncogenic lncRNA in pancreatic cancer and regulates the Wnt/β‑catenin signaling pathway via miR‑577

Abstract: The objective of the present study was to clarify the expression characteristics of long non-coding RNA (lncRNA) FGD5 antisense RNA 1 (FGD5-AS1) in pancreatic cancer, as well as its biological function and underlying mechanism. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was utilized for the detection of FGD5-AS1 and microRNA (miR)-577 expression levels in pancreatic cancer tissues. Transfection was performed to upregulate or downregulate FGD5-AS1 in pancreatic cancer cell lines. MTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…miR-1275 downstream target genes were predicted via TargetScan and miRDB online database and screened via Venn diagram to obtain eight intersecting genes ( Figure 6A ). Among them, AXIN2 was previously shown to be highly expressed in a variety of tumors ( 24 , 25 ), including pancreatic cancer ( 26 ), and plays a tumor-promoting role. However, the functions of AXIN2 on NK cells under hypoxic conditions remains vague.…”
Section: Resultsmentioning
confidence: 99%
“…miR-1275 downstream target genes were predicted via TargetScan and miRDB online database and screened via Venn diagram to obtain eight intersecting genes ( Figure 6A ). Among them, AXIN2 was previously shown to be highly expressed in a variety of tumors ( 24 , 25 ), including pancreatic cancer ( 26 ), and plays a tumor-promoting role. However, the functions of AXIN2 on NK cells under hypoxic conditions remains vague.…”
Section: Resultsmentioning
confidence: 99%
“…Downregulation of FGD5-AS1 led to increased levels of miR-577, resulting in decreased levels of β-catenin and LRP6. This decrease was associated with a reduction in the Wnt signaling pathway and inhibition of cell proliferation, migration and invasion [55] . CERS6-AS1 (ceramide synthase 6 antisense RNA 1) was also identified as being overexpressed in both pancreatic tissue samples and cell lines [56] .…”
Section: Selected Cancer-related Ncnatsmentioning
confidence: 98%
“…FGD5-AS1 (FGD5 antisense RNA 1) was shown to be overexpressed in pancreatic cancer and bind to miR-577, which targets β-catenin and LRP6 (low‑density lipoprotein receptor‑related protein 6) [55] . Downregulation of FGD5-AS1 led to increased levels of miR-577, resulting in decreased levels of β-catenin and LRP6.…”
Section: Selected Cancer-related Ncnatsmentioning
confidence: 99%
“…In the same study, it was shown that FGD5-AS1 activates the Wnt/β-catenin signaling pathway by suppressing miR-577, a tumor suppressor in PC. It was reported that the expression of NUTF2P3-001, another lncRNA that increases in cases of hypoxia, plays a positive role in the regulation of KRAS expression and supports cell proliferation in PC [ 39 ].…”
Section: Lncrnas In Pancreas Cancermentioning
confidence: 99%